Variation in the degree of Continentality climate of Iraq (Journal of the College of Education for Women, 2019)
This research paper is about thevariationin the degree of Continentality climate of theIraq during (40) years for a number of climate station. Using Poresof formula, it is found outthat the climate of Iraq ranges between extreme Continentality and very extremeContinentality, and that the Continentality degree is characterized with extreme frequencyfrom one year to another. In certain years, the degree of climate Continentality decreaseswhile in other years it rises in such a way that there is no similarity in the Continental degreefrom one year to another for the same station.As for the general trend of the degree of Continentality, the last years had noticedspecial variations, which are divided in to three climate regions: the first region exists in theNorth and North-East of the country in which the Continentality degree tended to decreaseand it is ranged between-0.2% to -0.6%,while the Continentality degree of the second region,which is located in the middle and north of the country, tended to rise simply and this rangedbetween 0.6% to 1.7%. Finally, the Continentality degree of the third region, which is locatedin the south-east tended to a most clear rise which ranged between 2.5% to 8.7%.By drawing maps of the annual Continentality degree, it is found out that in someyearsthe area of the extreme Continentality climate and the very extreme Continentalityclimate are equal, while in other years, the area of the extreme Continentality climatebecomes much wider and the opposite happens in other years.